2020
DOI: 10.1021/acsomega.0c00869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potential to Modify Pulp and Paper Properties through Oxygen Delignification

Abstract: The potential to modify pulp and paper properties by oxygen delignification was assessed by looking beyond the ordinary purpose of oxygen delignification. Pulps with the same kappa number were obtained by both pulping and the combination of pulping and oxygen delignification, and the mechanical and chemical properties were compared. The oxidation of pulp components leads to an increase in carboxylic acid groups in the fibers, resulting in a large influence on fiber swelling, seen as an increase in the water re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(60 reference statements)
3
10
0
Order By: Relevance
“…3, the amount of charged groups, in the pulp samples, decreased with continued kraft cooking (solid line); pulp with lower kappa number had less charged groups. This is in accordance with previous studies (Buchert et al 1997;Chai et al 2003;Dang et al 2006;Esteves et al 2020). In unbleached pulp fibers the main charged groups are the phenolic groups in the lignin structure, mainly guaiacyl units in softwood (Ragnar et al 2000) and the carboxylic groups in xylan (Bhardwaj et al 2004;Dang et al 2006).…”
Section: Fiber Chargesupporting
confidence: 91%
“…3, the amount of charged groups, in the pulp samples, decreased with continued kraft cooking (solid line); pulp with lower kappa number had less charged groups. This is in accordance with previous studies (Buchert et al 1997;Chai et al 2003;Dang et al 2006;Esteves et al 2020). In unbleached pulp fibers the main charged groups are the phenolic groups in the lignin structure, mainly guaiacyl units in softwood (Ragnar et al 2000) and the carboxylic groups in xylan (Bhardwaj et al 2004;Dang et al 2006).…”
Section: Fiber Chargesupporting
confidence: 91%
“…The importance of charged groups for the joint and network strength has also been recognized in the literature (Dang et al 2006;Esteves et al 2020;Hirn and Schennach 2015;Laine and Stenius 1997;Yang et al 2003;Zhang et al 2005Zhang et al , 2007Zhao et al 2016). It is known that oxygen delignification increases fiber charges and it apparently makes a much more important contribution to the final paper properties than was previously realized.…”
Section: Introductionmentioning
confidence: 79%
“…The refining of unbleached fibers is not commonly studied; however, it would be important to understand its impact in order to comprehend the following procedures and fiber modifications. In our previous work (Esteves et al 2020), it was concluded that charged groups enhance the development of tensile strength during refining. Cooked and oxygen delignified pulps with similar chemical compositions were compared, and it was shown that the mechanical strength could be increased by oxygen delignification if the fiber charge level was sufficiently high.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations